A little hope : a novel - Joella, Ethan (Scribner, 2021)
"How do you hold onto hope in a difficult time? In the small city of Wharton, Connecticut, lives are beginning to unravel. A woman loses the love of her life. A son struggles with addiction. A widow misses her late spouse. A husband betrays his wife. At the heart of these interlinking stories is one couple: Freddie and Greg Tyler. Greg has just been diagnosed with multiple myeloma, a brutal form of cancer. He has never been dependent or weak, and wants to overcome this the way he has succeeded at everything else: through grit and determination. But can Greg fight his illness? How will Freddie and their daughter cope if he doesn't? How do the other residents of Wharton learn to live with loss and to find happiness again? A debut that pulls at the heartstrings and immerses readers in a community, A Little Hope broadcasts the joy and hope to be found in the everyday acts of loving, forgiving, and surviving"--